Enhanced field emission properties of doped graphene nanosheets with layered SnS2 - Rout, Chandra Sekhar; Joshi, Padmashree D.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Simbeck, Adam J.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (Applied Physics Letters, 2014)
We report here our experimental investigations on p-doped graphene using tin sulfide (SnS2), which shows enhanced field emission properties. The turn on field required to draw an emission current density of 1 mu A/cm(2) is significantly low (almost half the value) for the SnS2/reduced graphene oxide (RGO) nanocomposite (2.65 V/mu m) compared to pristine SnS2 (4.8 V/mu m) nanosheets. The field enhancement factor beta (similar to 3200 for the SnS2 and similar to 3700 for SnS2/RGO composite) was calculated from Fowler-Nordheim (F-N) plots, which indicates that the emission is from the nanometric geometry of the emitter. The field emission current versus time plot shows overall good emission stability for the SnS2/RGO emitter. The magnitude of work function of SnS2 and a SnS2/graphene composite has been calculated from first principles density functional theory (DFT) and is found to be 6.89 eV and 5.42 eV, respectively. The DFT calculations clearly reveal that the enhanced field emission properties of SnS2/RGO are due to a substantial lowering of the work function of SnS2 when supported by graphene, which is in response to p-type doping of graphene. (C) 2014 AIP Publishing LLC.